Utility of serum gamma glutamyl transferase activity among hypertensive patients - Kunwar, Saroj; Maharjan, Luniva; Chaulaigai, Bimal; Sah, Sanjay Kumar (International Journal of Scientific Reports, 2019)
Background: Hypertension, a chronic medical condition of elevated blood pressure in the arteries. It is an emerging problem worldwide and one of the identifiable cause of kidney disease. Gamma glutamyl transferase (GGT) plays essential role in the metabolism of glutathione which is reported as major antioxidant. More recently increased GGT is associated with pathogenesis of hypertension. This study was aimed to determine activity of gamma glutamyl transferase in hypertensive patients. Methods: All together 150 participants were recruited from Department of Medicine, Star Hospital for this hospital based cross-sectional study. Among which 50 were normotensive, 50 were pre-hypertensive and 50 were hypertensive. Blood sample were collected and analyzed in autoanalyser by enzymatic method. Results: Mean serum gamma glutamyl transferase activity is significantly different among normotensive, prehypertensive and hypertensive groups (i.e., 10.3 IU/l, 26.8IU/l and 37.2 IU/l respectively). Serum gamma glutamyl transferase activity is significantly higher in prehypertensive patients than normotensive group (p=0.001). Similarly GGT activity is significantly increased in hypertensive patients than prehypertensive patients (p=0.001). Conclusions: Serum gamma glutamyl transferase activity is raised in prehypertensive and hypertensive participants as compared to normotensive. Thus Serum gamma glutamyl transferase level can have potential role on management of hypertension.